Perempuan Sebagai Agen Perubahan Sosial-Ekonomi Masyarakat Pesisir Sekitar PLTH (Pembangkit Listrik Tenaga Hybrid) Pantai Baru, Kabupaten Bantul, Daerah Istimewa Yogyakarta - Derajad S. Widhyharto (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2015)
Limitations and scarcity of natural energy resources has forced the government to develop new renewable energy, one of them by making a pilot hybrid power plant project or Pembangkit Listrik Tenaga Hybrid (PLTH) in coast Pantai Baru, Pandansimo, Bantul. It is an innovative attempt at once problematic, innovative efforts appear because electricity that facilitated community and business opportunity to improve their welfare. Instead, the change still leaves the problem and contestation among stakeholders. Vulnerable groups like women are the groups that most affected by such change. They perform a dual role at the domestic level as well as the public, unfortunately these changes make them as objects rather than subjects of the new renewable energy projects. An effort to shift the women from the position of an object to be the subject of renewable energy is not easy task. In response, the methodological attempt to do is to choose action research to strengthen women as agents of change in the post-construction PLTH. The result, although not all involved, a group of coastal women can no longer be considered vulnerable, but it has become one of the new strengths of coastal communities around PLTH.